1999
DOI: 10.1016/s0892-6875(99)00111-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of electrode probes in determinations of filter cake formation and batch filter scale-up

Abstract: A well controlled apparatus was used to obtain new data for constant pressure cake formation in a batch leaf filter which could be fitted with electrode type sensing probes. For aqueous suspensions of calcite and talc, the influence of the intrusive electrodes on cake formation was quantified with respect to filtration parameters. As the electrode length and diameter were altered such that the projected cross-sectional area occupied up to 2.6% of the filter area, the average specific cake resistance (as determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These were positioned at 1 mm vertical intervals above the filter medium and protruded circa 2 mm from the cell walls; previous work has shown that such intrusions cause negligible effects on cake formation [Tarleton, 1999b]. Signals to each electrode pair were switched by the computer via electronic circuitry to give electrical resistance measurements of changing cake thickness and solids concentration.…”
Section: Methodsmentioning
confidence: 99%
“…These were positioned at 1 mm vertical intervals above the filter medium and protruded circa 2 mm from the cell walls; previous work has shown that such intrusions cause negligible effects on cake formation [Tarleton, 1999b]. Signals to each electrode pair were switched by the computer via electronic circuitry to give electrical resistance measurements of changing cake thickness and solids concentration.…”
Section: Methodsmentioning
confidence: 99%
“…equation and/or force analysis have been developed to estimate cake porosity [2][3][4][5]. Use of electrode type sensing probes [6] and high-energy radiation [7] have also been attempted to measure the cake porosity. Nevertheless, these methods have a limitation that they are nothing but indirect analysis of cake porosity.…”
Section: Introductionmentioning
confidence: 99%
“…The effective pressure increases from the top of the filter cake downward to the filter medium as a result of the frictional drag between the liquid and the solid particles 27–30. Furthermore, compressible filter cakes become compressed when the effective pressure increases, so solid volume fraction is higher near the filter medium than at the top of the cake 7, 30–32. Moreover, solid volume fraction is important when modeling filtrations because the specific filter‐cake resistance is a function of solid volume fraction, as described previously.…”
Section: Traditional Cake Filtration Theorymentioning
confidence: 96%